Digital food culture, power and everyday life. (December 2021) - Feldman, Zeena; Goodman, Michael K.
Food and digital culture are mutually implicated in contemporary processes of knowledge production and power contestation around the world. Our introduction and the papers in this special issue of the European Journal of Cultural Studies seek to draw out the distinctions, parallels and overlaps across food and the digital to offer critical insights into digital food culture's capacities, paradoxes and impacts on everyday life. We ask a series of questions fundamentally focused on issues of power that signal a critical concern for the (re)production and circulation of inequality within the food and digital nexus. For us and the authors here, Cultural Studies is particularly fertile ground from which to analyse digital food culture precisely because of the discipline's commitment to critiquing power and inequality and its subsequent capacity to illuminate everyday digital food politics and their social, cultural and ethical impacts. This article presents and highlights key questions—and introduces related concepts and theoretical debates—that drive this research agenda. In addition, we address the ways the issue's papers connect to digital food culture and power after COVID-19. We conclude with a summary of the articles in the issue and their contributions to digital food culture research and cultural studies more broadly.